(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The demands for broiler meat are increasing due to population whereas production cost of such meat has remained high due to high cost of convectional feed. Carcass and organ weight characteristics of ninety-six (96) 2-weeks old broiler birds fed dried watermelon peel meal was investigated. Watermelon peel meal was included at 0, 1.25, 2.5 and 3.75% dietary inclusion levels as replacement for wheat offal to form (Diet 1, Diet 2, Diet 3 and Diet 4 respectively). The birds were randomly allocated to four treatment groups replicated thrice to have 8 birds per replicate, and were fed the experimental diets ad libitum for 4 weeks under a deep litter management system. At day 28, one bird replicate was slaughtered for the evaluation of carcass and organs weight characteristics. There were no significant (P>0.05) differences in live weight, carcass weight, dressing %, thigh, shank, wing and neck. Significantly (P<0.05) higher breast muscle of 109.67g/bird was recorded on birds fed 3.75% DWMP compared to other groups. For the organs weight, no significant effect on liver, heart, lung, intestine, pancreas and gizzard (P>0.05). Based on the carcass and organs weight characteristics of birds, dried watermelon meal can be included up to 3.75% in the diet of birds at the starter phase without any harmful effect on their carcass and organs.